Cancer Management and Therapy - Hamza, Amal; Salem, Neveen (IntechOpen, 2018)
There are many different types of cancer. Some are very common; others are rare. Having some similar features, each cancer has its own characteristics and symptoms, which vary according to the type of cancer and where it is in the body. The treatment selected may be influenced by the patient's age, concurrent health problems, life expectancy, characteristics of the individual's cancer, the patient's goals of treatment, and the bias of the treating physician. In preparing this book, we have considered and reflected on the concept of the recent advances in cancer management and therapy as well as molecular applications in cancer therapy. The readers can find detailed information about the treatment and management of specific cancers in these book chapters.